State-sanctioned violence: advancing a social work social justice agenda - Delgado, Melvin (Interpersonal violence series, 2020)
"A book on a controversial topic such as U.S. state sanctioned violence questions many of our basic assumptions we hold true. The importance of violence is well attested to by Oxford University Press devoting a Book Series on Interpersonal Violence. However, state sanctioned violence in the U.S. is not, for example. The saying "The truth will set you free, but first it will make you miserable" comes to mind in writing this book because it holds personal meaning for me that goes beyond being a social worker and a person of color (Latinx). The basic premise and interconnectedness of the themes in this book were reinforced and expanded in the course of writing. Bonilla-Silva (2019, p. 14) states "We are living, once again, in strange racial times," and yes, indeed, we are. My hope is that readers appreciate the numerous threads between themes, some of which have not gotten close attention by the general public and scholars. Harris and Hodge (2017), for example, adeptly interconnect environmental, food, and school-to-pipeline among urban youth of color, illustrating how oppressions converge. Future scholarship will connect even more dots to create the mosaic that constitutes state sanctioned violence. I was relieved to see the extent of scholarship on the topics addressed in this book. Bringing to together this literature, public reports, and the experiences from those currently dealing with state sponsored violence, allowed for a consistent narrative to unfold. Writing a book is always a process of discovery. There is a body of scholarship to buttress the central arguments of this book, but no such literature addressing the structural interconnectedness of the types of state sanctioned violence for social work. The socio-political interactional consequences of place, time, people, and events, sets a social-political context that is understood by social workers and makes our mission distinctive because of this grounding. Viewing state sanctioned violence, including its laws and policies, within this prism allows us to develop a vision or charge that can unite us, as well as a deeper commitment to working with oppressed groups in seeking social justice. Social work is not exempt from having a role in state sanctioned violence. We only to delve into the profession's history and evolution to appreciate how we have reinforced a state sanctioned violence agenda, wittingly or unwittingly. Practice is never apolitical; they either support a state sanctioned violence ...